A Koli man makes his way to a Ganapati shrine - Mumbai Archive Project Team (Jio Institute, 2024)
A Koli man makes his way to a Ganapati shrine, walking over a causeway that is accessible only during low tide. During high tide, the shrine goes underwater, and its location is marked only by the flags sticking out from the surface.